FINANCIAL ECONOMY OF THE SELECTED COMMUNE IN 2020-2022 - Irena Kropsz-Wydra; Alicja Pakuła (Annals of the Polish Association of Agricultural and Agribusiness Economists)
The aim of the article is to analyze and assess the financial condition of the Jelcz-Laskowice commune. The financial management of the commune reflects effective budget management and shows its ability to function independently and develop further. The analysis of the commune’s budget is a tool for assessing its condition and the effectiveness of the actions taken, while the indicator analysis is the starting point for local government units in planning and implementing future budget expenditures. The assessment of the Jelcz-Laskowice commune was carried out in 2020-2022. The analysis used indicators to assess the financial condition of local government units, i.e.: budget indicators, per capita indicators, liabilities indicators by debt titles and indicators assessing the development potential of the commune. The obtained results indicate an improvement in the financial condition of the Jelcz-Laskowice commune. The increase in the income and expenditure independence indicator of the commune suggests that the unit is becoming more financially independent, which indicates the increased ability of the commune to manage its finances independently. The share of own revenues and operating surplus in total budget revenues showed an upward trend, remaining at a stable level. The Jelcz-Laskowice commune demonstrated stable financial development and effective budget management in the analysed period.